Experiences and social determinants of sexual violence and post-violence help-seeking behaviour among children and young people in Kenya - Okova, Denis; Toska, Elona; Bounagnin, Bolade (Health Economics Unit, 2024)
This dissertation examined the social determinants of sexual violence experience and help- seeking among Kenyan young men and women. Sexual violence is a public health concern because its levels are unacceptably high in Kenya, and it is a known risk factor for HIV infection.This is an urgent issue because Kenya has the third-largest HIV epidemic in the world and almosthalf of new HIV infections occur among young people. Therefore, preventing sexual violence is only possible if predictors of sexual violence and response pathways are continuously investigated. This study used Kenya's 2019 Nationally Representative Violence against Children Survey (VACS) data focusing on young men and women aged 13-24 years old. Sexual violence was defined as reporting unwanted touching, forced sex, attempted forced sex, or experiencing physical forced sex/rape, either in one's lifetime or in the past year both of which were binary variables. Help-seeking behavior was indicated by knowing where to seek formal help, seeking formal help, receiving formal help, and informal disclosure all of which are binary variables. This study first documents the pathway of sexual violence from exposure to help-seeking among young men and women in Kenya. Logistic regression models were then fitted to investigate predictors of sexual violence experience over the past year and lifetime disclosure of sexual violence in young women, controlling for age, being in a relationship, education status, HIV/AIDS testing, orphanhood, and household poverty. This study had 1344 female and 788 male participants. Young women reported a higher lifetime prevalence of sexual violence compared with young men (25.2% vs. 11.4%, p=0.000). Of these lifetime experiences of sexual violence, more young women than young men informally disclosedthese acts (45.1% vs. 22.7%, p=0.002). Although 33.7% of young women and 33.1% of young men knew where to seek formal help after experiencing sexual violence, more young women thanyoung men sought formal help after experiencing sexual violence (11.3% vs 6.8%, p=0.248). Gender inequitable attitudes [AOR 3.07 (1.10–8.56); p=0.032], experiencing emotional violence at home [AOR 2.11 (1.17–3.81); p=0.014], and cyberbullying [AOR 5.90 (2.83–12.29);p=0.000] are risk factors for sexual violence among young women. Life skills training [AOR 0.22 v (0.07– 0.73); p=0.014] and positive parental monitoring [AOR 0.31 (0.10–0.99);p=0.048] are protective against sexual violence among young women. Positive parental monitoring [AOR 3.85 (1.56– 9.46);p=0.004] was also associated with increased likelihood of informal disclosure among young women. This study highlights the protective value of life skills training and positive parental monitoring in sexual violence prevention. Moreover, this analysis demonstrated the possible role of gender inequitable attitudes, cyberbullying, and emotional violence at home in fueling sexual violence. Future VACS might consider increasing sample sizes to increase robustness of analyses, especially on help-seeking.